EFEKTIVITAS PENGELOLAAN PERAHU ENYEBERANGAN SUNGAI JENEBERANG DI DESA TAENG KABUPATEN GOWA SEBAGAI ALTERNATIF TRANSPORTASI UMUM - Imanuddin, Imanuddin; Mahsyar, Abdul; Muhiddin, Amir (Universitas Muhammadiyah Makassar, 2024)
The aim of this research is to examine the effectiveness of boats crossing the Jeneberang River as an alternative public transportation in Taeng village, Gowa district. The aim of this research is to find out how effective the management of boats crossing the Jeneberang River is in meeting public transportation needs in Taeng Village, Gowa Regency. The type of research used is qualitative research, the data sources used are primary and secondary. Data collection uses observation, interview and documentation techniques. The results of the research show that the effectiveness of ferry boat management as an alternative to public transportation in Taeng Village, Gowa Regency, is an indicator of achieving goals that have been effective in terms of service to transportation users. In terms of integration, the effectiveness of ferry boats is not yet optimal due to the lack of satisfaction in handling the causes of boat accidents. And from the adaptation indicators it cannot be said to be effective because the management of ferry boats in terms of providing innovation to ferry boat users still seems slow in providing adjustments such as inadequate supporting infrastructure (facilities and infrastructure).